Figure eretiche e conflitti socioculturali ne "Il nome della rosa", fra serie tv e romanzo - Montanari, Federico (Mediascapes journal, 2020)
The intention of this article is to analyze and discuss, from a socio-semiotic and media theory point of view, some emerging narratives and discursive figures, starting from the novel by Eco (1980), from its film adaptation (1986), but above all to get to the new Tv series (2019). We will discuss the "figure of the heretic", also considering the scientific and general interest that this multiple image has always aroused, of course, also starting from the studies on the Middle Ages. We will consider some characters, as they are built within the novel of Eco, trying to see how they reticulate above all in the adaptation to a television series, with the aim of understanding their genesis and the transformation of those figures and their discursive devices (as well as ideological and axiological one). And also providing a broader reference to the recent panorama of media and Tv studies, applied to digital media and social media; but also trying to evaluate the "subtextual" network and the textual archipelago (like historical references, both medieval and contemporary) created by Eco. Finally considering it as a starting point for a possible reasoning on the "palimpsestual" forms of current media phenomena, including social media and cross- and trans-media narrative practices.